Effect of neridronate on axial involvement in patients with spondyloarthritis when biologics are not possible. Results of a monocentric study - Crotti, Chiara; Di Taranto, Raffaele; Orsini, Francesco; Ferrito, Matteo; Varenna, Massimo; Favalli, Ennio Giulio; Caporali, Roberto (Frontiers in Medicine, 2023)
Introduction. To examine the potential effectiveness of intravenous neridronate (IVNer) on axial involvement in patients with spondyloarthritis (SpA) refractory to nonsteroidal anti-inflammatory drugs (NSAIDs) but not eligible for biological disease-modifying antirheumatic drugs (bDMARDs). Method. Patients with active SpA (BASDAI score ≥4) and active sacroileitis (SI) on MRI (according to ASAS MRI definition), who were NSAIDs-insufficient responder/intolerant but not eligible for bDMARDs were retrospectively recruited in a tertiary Rheumatology Centre between Sept 2015 and Dec 2021. IVNer (100 mg) was given on days 1, 4, 7, and 10. Response was evaluated sixty days after the last infusion as the median change from baseline of BASDAI and visual analogue scale (VAS) pain, and improvement on MRI signs.Results. 38 patients (26 axial SpA, 3 enteropathic arthritis, and 9 axial psoriatic arthritis) were included (66% females, mean age±SD 38.0±14.1 yrs, mean disease duration 30.5±49.5 months [range 1.0-298], 47% HLAB27+). The reason for bDMARD ineligibility was concurrent solid (n=6) or hematological (n=1) malignancy, comorbidities (n=11), or patient preference (n=20). Both median